First-degree relatives of suicide completers may have impaired decision-making but functional cognitive control. (September 2015) - Hoehne, A.; Richard-Devantoy, S.; Ding, Y.; Turecki, G.; Jollant, F.
Abstract: Background: The heritability of suicide is well established. Transmission of risk appears to follow traits more than disorders like depression. In the present project, we aimed at investigating the potential for transmission of cognitive deficits previously observed in suicide attempters, specifically impaired decision-making and cognitive control. Methods: Seventeen healthy first-degree relatives of suicide completers with no personal history of suicidal act were compared to 18 first-degree relatives of individuals with major depressive disorder but no family history of suicidal act, and 19 healthy controls. Decision-making was assessed with the Iowa Gambling Task, and cognitive control with the Stroop Task, the Hayling Sentence Completion Test, and the Trail-Making Test. Results: Both suicide and depressed relatives showed lower gambling task net scores than healthy controls. However, there were trends toward lower learning abilities in suicide than depressed relatives (interaction: p = 0.07), with more risky choices at the end of the test. Suicide relatives also showed a higher number of self-corrected errors relative to the total number of errors in the Stroop colour test compared to both control groups, with no difference in interference scores. There was no group-difference for any other cognitive tests. Conclusion: Our findings suggest that decision-making impairment may be found in healthy relatives of suicides and represent a cognitive endophenotype of suicidal behaviour. Normal cognitive control (or self-corrected deficits) may protect relatives against suicidal acts. Impairments in value-based and control processes may, therefore, be part of the suicide vulnerability and represent potential targets of preventative interventions. Graphical abstract: Highlights: Deficits in value-based decision-making and cognitive control have previously been found in suicide attempters. Here, we report disadvantageous decision-making in first-degree relatives of suicide completers. Risky decision-making may therefore be a heritable endophenotype of suicide. Normal cognitive control could be a protective factor against suicide in this population.